COMMODIFICATION OF RELIGION IN HOUSING - Hamzah Muchtar, Evan (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
Indonesian society is pluralistic—many different ethnicities, cultures, and religions. One of the things that are currently booming is related to religious issues. The religion in question is Islam because the Indonesian people are the majority of the Muslim community. With the Muslim majority community, this is the field of business oriented capitalists. This capitalist tries to marry all business activities with the Islamic religion, called the commodification of religion. This study aims to describe the commodification of religion in terms of property, namely sharia housing. This research uses a Qualitative method. The Result Basically, the concept of sharia housing marries the idea of conventional housing that has existed before with the concept of religion to form a new lifestyle and identity among urban communities; marketing strategies with the gathering concept are various ways that developers use using religious symbols to sell their products. The use of religious symbols in the sale of sharia housing is considered a form of religious commodification.